PENGARUH HARGA DAN AKSESBILITAS TERHADAP MINAT BERKUNJUNG DAN PENINGKATAN PELAKU WIRAUSAHA DI DESTINASI DANAU CIPONDOH - Heny Ratnaningtyas; Myrza Rahmanita; Fetty Asmaniati (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
This study aims to determine the effect of price and accessibility on visiting intentions and their effect on increasing entrepreneurial actors in Lake Cipondoh. This type of research is descriptive quantitative using the path analysis method. The population of this study consisted of all visitors to Lake Cipondoh, and the number of samples used was 150 respondents. The sampling technique uses accidental sampling. The results of the study show that (1) Price and accessibility have a significant effect on visiting intentions; (2) Interest has a significant effect on increasing the number of entrepreneurs. Research conducted by Nurbaeti et al. (2021) aligns with this research, which shows that parking ticket fees, entrance tickets, and entertainment prices are very cheap and affordable. Therefore, visitors are interested in visiting tourist destinations that are more affordable financially. Paved and concrete roads, many and varied types of public transportation, and clear road signs make visitors interested in coming to tourist destinations. Interest in visiting tourist destinations influences the increased demand for food and beverages, providing business actors with opportunities to establish food and dining stalls in tourist destinations.